Association between 1,5-Anhydroglucitol and Acute C Peptide Response to Arginine among Patients with Type 2 Diabetes - Yun Shen; Yiming Si; Jingyi Lu; Xiaojing Ma; Lei Zhang; Yifei Mo; Wei Lu; Wei Zhu; Yuqian Bao; Gang Hu; Jian Zhou (Journal of Diabetes Research)
Objective. The aim of this study was to explore the association of 1,5-anhydroglucitol with acute C peptide response (ACPR) to arginine among patients with type 2 diabetes. Methods. Patients with type 2 diabetes were enrolled from the Department of Endocrinology and Metabolism, Shanghai Sixth People’s Hospital. ACPR was assessed using arginine stimulation test. Decreased β-cell function was defined as ACPR<2.1. Multivariable logistic regression models were used to demonstrate the association between 1,5-anhydroglucitol and decreased β-cell function. Results. Finally, 623 patients with type 2 diabetes were enrolled into the analysis. Multivariable-adjusted odds ratios for decreased β-cell function across quartiles of 1,5-anhydroglucitol were 1.00, 0.47 (95% confidence interval (CI) 0.23-0.99), 0.41 (95% CI 0.20-0.84), and 0.27 (95% CI 0.13-0.57) (Ptrend=0.042), respectively. When 1,5-anhydroglucitol was considered as a continuous variable after logarithm, the corresponding odds ratio was 0.40 (95% CI 0.23-0.71). Conclusions. We demonstrated a dose-response linear association between 1,5-anhydroglucitol and ACPR. 1,5-Anhydroglucitol was likely to be associated with β-cell function. Further analysis with large sample size and prospective study design is warranted to validate our findings.